Risk assessments questions and answers : a practical approach - Perry, Pat, 1954- (ICE Publishing, 2016)
'Risk Assessments Questions and Answers' is a practical handbook providing best practice solutions to a comprehensive set of frequently asked questions about risk assessments. This work explains and covers approved codes of practice, legal requirements and the latest guidance on a wide range of health and safety topics.
This edition previously issued in print: 2016.
Keywords: Industrial safety -- Evaluation.; Risk assessment.; elektronické knihy; electronic books